Aminium cation-radical catalysed selective hydration of (E)-aryl enynes. Issue 57 (22nd June 2021) - Giel, Marie-Claire; Barrow, Andrew S.; Smedley, Christopher J.; Lewis, William; Moses, John E.
Abstract : A new selective method for the mild and metal-free catalytic Markovnikov hydration of ( E )-aryl enynes to the corresponding enones, mediated through the bench-stable aminium salt, tris(4-bromophenyl)ammoniumyl hexachloroantimonate (TBPA), is reported. Abstract : The hydration of carbon–carbon triple bonds is an important and atom economic synthetic transformation. Herein, we report a mild and selective method for the catalytic Markovnikov hydration of ( E )-aryl enynes to the corresponding enones, mediated through the bench-stable aminium salt, tris(4-bromophenyl)ammoniumyl hexachloroantimonate (TBPA). The chemoselective and diastereoselective method proceeds under neutral metal-free conditions, delivering excellent product yields from terminal and internal alkyne units. The synthesis of biologically important ( E )-3-styrylisocoumarins, including a formal synthesis of the natural product achlisocoumarin III, demonstrates the utility of this novel transformation.